EVALUASI SISTEM PENGENDALIAN INTERNAL PADA SIKLUS PENDAPATAN DAN PEMBAYARAN KAS (STUDI KASUS PADA RETAILER SEPATU CABANG NGANJUK) - IKA INTAN PRAWESTY, RISTRA (: 2303-1719)
This Shoe retailer has 297 branches all over Indonesia today. The shoe retailer has actually implementing internal control, but it still found that the internal control of this shoe retailers still have some weaknesses, particularly in Nganjuk.. This are common problems in the branch store shoe retailer, but the primarily to store Nganjuk region. Besides the division of labor has not been properly informed. There is also over lapping inside the store. This study evaluated the system of internal control in shoe retailer Nganjuk branch of the revenue cycle and cash payments. Objectives expected to be achieved in this study was to evaluate the internal controls. The interviews conducted in this thesis for shoe retailer company employees at headquarters and branch. Inspection of documents recording conducted by COSO mapping application by marking documents or entities with standard symbols mapping COSO. It is also comparing what happens in the field process to the reference literature. The results of the inspection will be outlined and analyzed through COSO. Internal control branch Nganjuk shoe retailer found to be less effective, mainly due to a massive loss of cash proceeds from the sale which is still going on.